SEJARAH PELABUHAN PENYEBERANGAN RO-RO DI KABUPATEN BENGKALIS TAHUN 1995-2019 (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: Bengkalis Regency is part of its territory located in Bengkalis Island and Sumatra Island, this has become one of the obstacles, namely maritime transportation, therefore a Bengkalis (roll-on roll-of) ferry port was built. The objectives of this study are: (1) to determine the background of the development of the Ro-Ro Bengkalis harbor, (2) to determine the physical development of the Ro-Ro Bengkalis harbor, (3) to determine development of ferry flows in the Ro-Ro Bengkalis port. This research uses a qualitative approach. A qualitative approach was taken to find out the history of the Ro-Ro Ferry Port in Bengkalis Regency. The results of this survey are: (1) Ro-Ro Bengkalis Ferry Port was built in 1995 by the Riau Provincial Government and handed over to the Bengkalis Government in 2000. This ferry port of Ro-Ro Bengkalis is also called the crossing port. Putih-Sungai Selari, (2) the physical development of the port from the beginning of the development to now, has always been through development, such as adding dock, expanding the parking lot and so on, this is to provide service and comfort to passengers, (3) crossing the stream from the start of the operation So far it continues to experience significant improvements, this is because sea transportation using Ro-Ro is seen as the best alternative in terms of economy and efficiency.Key Words: History, Ro-Ro Port, Bengkalis